Vietnam's post-1975 agrarian reforms : how local politics derailed socialist agriculture in southern Vietnam - Dang, Trung Dinh (Vietnam series (Acton, A.C.T.), 2018)
"This book investigates why collectivised farming failed in south Vietnam after 1975. Despite the strong will of the new regime to implement collectivisation, the effort was uneven, misapplied and subverted. After only 10 years of trying, the regime annulled the policy. Focusing on two case studies--Quảng Nam province in the Central Coast region and An Giang province in the Mekong Delta--and based on extensive evidence, this study argues that the reasons for variations in implementation and the failure and reversal of the policy were twofold: regional differences and local politics."